2020
DOI: 10.1038/s41598-020-69645-0
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated algal feeds as a sustainable replacement diet for broodstock in commercial bivalve aquaculture

Abstract: The global bivalve shellfish industry makes up 25% of aquaculture, is worth USD $17.2 billion year −1 , and relies upon a supply of juvenile bivalves produced by adult broodstock in hatcheries. Today large quantities of live algae are grown to feed broodstock at $220 kg −1 , driving highly unsustainable energy and resource use. New advances in algal and microencapsulation technology provide solutions. We developed microencapsulated Schizochytrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Consequently, considerable research is currently underway to develop artificial feeds that could reduce dependence on live microalgae for feeding juvenile shellfish (Carboni et al, 2016;Libini et al, 2017;Mazón-Suástegui et al, 2017;Willer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, considerable research is currently underway to develop artificial feeds that could reduce dependence on live microalgae for feeding juvenile shellfish (Carboni et al, 2016;Libini et al, 2017;Mazón-Suástegui et al, 2017;Willer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Seafood processing of mackerel redirected to human markets would theoretically still retain 47,321 t of by-products (that is, the inedible portion), which could partially replace marine ingredient supply. Across all species, allocating 100% of ECM fish currently used as feed for human consumption would require an additional 69% of fish oil, either from new sources 28 30 or from more effective by-product usage. Redirecting feed fish for human food could produce 600,000 t of by-products for use as marine ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…oil can be an effective source of omega-3 for salmonids 28 and can be grown heterotrophically using sugar cane or beet by-products. There are trade-offs in environmental performance and cost compared with marine ingredients through high-energy consumption, but performance continues to improve and production is scalable 30 , 64 . Other ‘novel’ alternatives to fish oil, such as yeast oil or genetically modified omega-3 plant oils 28 , are also entering the market.…”
Section: Discussionmentioning
confidence: 99%
“…67 In addition it has been demonstrated that the use of inert feeds promotes lower CO 2 emissions, reduced energy and antibiotic use as compared with the production of live feeds. 68 The chronological, gradual replacement of live feeds by inert feeds has required multidisciplinary research, and the application of traditional and advanced nutritional methodologies has been of further assistance. Additional knowledge on nutritional physiology aspects has been acquired through the use of isotopic techniques, and this has in turn contributed to improve the feeding schemes for larval and juvenile stages of different edible and ornamental aquaculture species.…”
Section: Estimation Of Nutritional Contributions To Larval Growthmentioning
confidence: 99%